2011
DOI: 10.1111/j.1600-0609.2011.01706.x
|View full text |Cite
|
Sign up to set email alerts
|

Brain magnetic resonance angiography in splenectomized adults with β-thalassemia intermedia

Abstract: Cerebral vasculopathy is common in splenectomized adults with TI. However, large-vessel disease does not explain the occurrence of silent brain infarction. The combined use of MRA and MRI better identifies splenectomized TI adults with neuroimaging abnormalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 36 publications
2
46
0
1
Order By: Relevance
“…In the same cohort of patients, it was noted that 27.6% had evidence of arterial stenosis on magnetic resonance angiography. However, there was no association between large-vessel stenosis on magnetic resonance angiography and silent strokes identified on MRI, leaving small arteriolar pathology as the most likely explanation for these silent lesions [49]. This is further confirmed through studies evaluating transcranial Doppler ultrasonography velocities in TI patients [50].…”
Section: Thrombosis In Thalassemiamentioning
confidence: 73%
“…In the same cohort of patients, it was noted that 27.6% had evidence of arterial stenosis on magnetic resonance angiography. However, there was no association between large-vessel stenosis on magnetic resonance angiography and silent strokes identified on MRI, leaving small arteriolar pathology as the most likely explanation for these silent lesions [49]. This is further confirmed through studies evaluating transcranial Doppler ultrasonography velocities in TI patients [50].…”
Section: Thrombosis In Thalassemiamentioning
confidence: 73%
“…Recent studies, to be further illustrated in the subsequent section, have also documented a high incidence of silent brain infarction, large cerebral vessel disease, and decreased neuronal function, primarily in the temporal and parietal lobes, among splenectomized patients with TI Taher et al 2010d;Musallam et al 2011aMusallam et al , 2012a. Large-vessel cerebrovascular disease significantly correlated with higher NTBI levels (Musallam et al 2011a), and decreased neuronal function was observed more frequently in patients with elevated LIC (.15 mg Fe/g dw) (Musallam et al 2012a).…”
Section: Iron Overload and Target Organ Toxicitymentioning
confidence: 85%
“…Recent studies have also documented a high prevalence of large cerebral vessel disease (magnetic resonance angiography) and decreased neuronal function (positron emission tomography-computed tomography) primarily in the temporal and parietal lobes in similar patient cohorts. [66][67][68] A significant association between the occurrence of these abnormalities and elevated iron overload indices was noted. 67,68 In the general population, and in patients with sickle cell disease, these silent cerebrovascular abnormalities are associated with subsequent risk of overt stroke and neurocognitive decline, further highlighting the importance of these findings.…”
Section: 57mentioning
confidence: 92%
“…[66][67][68] A significant association between the occurrence of these abnormalities and elevated iron overload indices was noted. 67,68 In the general population, and in patients with sickle cell disease, these silent cerebrovascular abnormalities are associated with subsequent risk of overt stroke and neurocognitive decline, further highlighting the importance of these findings. 66 Another vascular complication of NTDT (primarily β-thalassemia intermedia and hemoglobin E/β-thalassemia) that was found to occur at a relatively high frequency compared to patients with β-thalassemia major is pulmonary hypertension.…”
Section: 57mentioning
confidence: 92%